Protective effect of chitosan oligosaccharide lactate against DNA double-strand breaks induced by a model methacrylate dental adhesive - Szczepanska, Joanna (International Scientific Literature, Inc., 2011)
BACKGROUND: Monomers of methacrylates used in restorative dentistry have been recently reported to induce DNA double-strand breaks (DSBs) in human gingival fibroblasts (HGFs) in vitro. Because such monomers may penetrate the pulp and oral cavity due to the incompleteness of polymerization and polymer degradation, they may induce a similar effect in vivo. DSBs are the most serious type of DNA damage and if misrepaired or not repaired may lead to mutation, cancer transformation and cell death. Therefore, the protection against DSBs induced by methacrylate monomers released from dental restorations is imperative. MATERIAL/METHODS: We examined the protective action of chitosan oligosaccharide lactate (ChOL) against cytotoxic and genotoxic effects induced by monomers of the model adhesive consisting of 55% bisphenol A-diglycidyl dimethacrylate (Bis-GMA) and 45% 2-hydroxyethyl methacrylate (HEMA). We evaluated the extent of DSBs by the neutral comet assay and the phosphorylation of the H2AX histone test. RESULTS: ChOL increased the viability of HGFs exposed to Bis-GMA/HEMA as assessed by flow cytometry. ChOL decreased the extent of DSBs induced by Bis-GMA/HEMA as evaluated by neutral comet assay and phosphorylation of the H2AX histone. ChOL did not change mechanical properties of the model adhesive, as checked by the shear bond test. Scanning electron microscopy revealed a better sealing of the dentinal microtubules in the presence of ChOL, which may protect pulp cells against the harmful action of the monomers. CONCLUSIONS: ChOL can be considered as an additive to methacrylate-based dental materials to prevent DSBs induction, but further studies are needed on its formulation with the methacrylates.